Evaluasi Karakteristik Pola Ruang Pasar Tradisional Lhoksukon Aceh Utara - safriana, U (Jurnal MESIL (Mesin Elektro Sipil), 2024)
The market is a meeting place for sellers and buyers to carry out transactions, a means of community transactions and community economic development. The traditional market is also one of the markets that is still developing at the present time and is the market most in demand by village communities for carrying out buying and selling transactions, and from some village communities, especially the Lhoksukon community, whose livelihood is as traders in traditional markets. In line with this, it states that service quality factors and consumer identification play an important part in encouraging consumers to shop or make repeat purchases at traditional markets, In market formation, there is a market space pattern which is a reference for forming market space in accordance with market needs, such as forming a space pattern in accordance with its function. And the formation of the traditional market space pattern is in accordance with existing standards, namely SNI 2015. This research aims to find the characteristics of traditional market space patterns to adapt to existing market standards. The object of research taken in this research is the Lhoksukon traditional market in terms of its conformity with 2015 SNI standards by knowing the pattern of trading space, facilities and infrastructure, accessibility and zoning. This research uses mixed methods. By getting in-depth information about the characteristics of traditional market space patterns that are in accordance with the 2015 SNI standards. Based on the research results, it shows that Lhoksukon traditional markets still do not comply with existing SNI standards.